Socio Psychology Characteristics of Women Who Had Their First Child - Nazarova Zarnigor (Genius Journals, 2023)
This article is devoted to the study of the social psychological characteristics of women before and after childbirth.
Keywords: psychic processes; individual psychological characteristics; psychosocial phenomenon; psychic States